Penerapan Zachman Framework dalam Perancangan Sistem Informasi Akademik biMBA AIUEO - Lia Lavivah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
biMBA-AIUEO is a Non-formal Early Childhood Education Institution using the biMBA program under the auspices of the Indonesian Child Development Foundation. biMBA stands for Interest guidance Reading and learning Children. So far, academic data processing has been less efficient and effective because it still uses a system that has not been integrated. So that data does not accumulate, the difficulty of finding the desired file, informing users, data storage and reporting requires a system that can optimize data management, reporting, and storage. With the design of the Academic Information System biMBA AIUEO can help speed up the admission process for new students and reduce errors in data processing. The Zachman Framework framework is one of the methods to assist all parties in defining a management as a whole that has a complete data structure. This research resulted in a website-based Academic information system to make it easier for the public to find information about biMBA AIUEO